A meta-analysis of flexible intramedullary nailing versus external fixation for pediatric femoral shaft fractures. Issue 5 (September 2016) - Guo, Yong Cheng; Feng, Guo Ming; Xing, Guang Wei; Yin, Jin Neng; Xia, Bing; Dong, Yan Zhao; Niu, Xue Qiang; He, Qianyi; Hu, Pengfei
Abstract : To compare the difference in efficacy following flexible intramedullary nailing (FIN) and external fixation (EF) for pediatric femoral shaft fractures. A systematic search was performed on PubMed, Embase, Medline, and Cochrane library for relevant studies. We included controlled trials comparing complications between FIN and EF for pediatric femoral shaft fractures published before 25 November 2014. Modified Jadad scores were utilized to assess the methodological quality of the studies included. The meta-analysis was carried out using Stata 12.0 software. Six studies involving 237 patients were included. On comparison of EF, a low incidence of overall complications [relative risk (RR)=0.30, 95% confidence interval (CI): 0.19–0.46; P <0.001] and pin-tract infection (RR=0.286, 95% CI: 0.13–0.61; P =0.001), but a high risk of soft tissue irritation (RR=1.86, 95% CI: 1.35–2.56; P <0.001) were found in patients treated with the FIN approach. No significant differences in other complications were found. On the basis of current evidence, the use of FIN leads to fewer complications than EF and may be considered as the first-line approach in the treatment of femoral shaft fractures. Abstract : Supplemental Digital Content is available in the text.